THE DISPUTE OF DAGESTAN THEOLOGIANS OVER THE RULES OF PERFORMING THE TARAWIH PRAYER IN THE LATE 19 – EARLY 20TH CENTURIES - Abdulmazidov, Ramazan Sultanovic; Alibekov, Hizri Gadzievic (History, Archeology and Ethnography of the Caucasus, 2021)
The paper studies the theological discussion around the performing of the prayer tarawih in Dagestan at the turn of the 19-20th centuries. The background of the issue in question is given in the introduction, revealing the origins of this controversy. The study focuses on several original Arabic-language works written by Dagestani theologians. Two parties participated in the discussion: Muslim al-Uradi and Kebedmuhammad al-Bezhti on the one side, and Usman al-Tsakhuri and Iman-Ali al-Bezhti – on the other. The paper reveals in detail the key arguments given by the opponents who participated in the polemic. It is worth noting that the authors of the works show a high level of proficiency in Arabic and theological knowledge. The Arabographic polemical works of Dagestani theologians allow us to outline the range of controversial issues that at various times troubled the minds of the Muslims of Dagestan. The article provides a chronological development of the discussion of the theologians, as well as a general analysis of the content of each of the works. The works under study were written within the framework of the Arab-Muslim manuscript tradition, some of them being autographs. It was found that Dagestani theologians, who mainly positioned themselves as strict adherents of the Shafi’i legal school, in some cases allowed themselves quite free views and disputed the opinions of leading Shafi’i legal scholars, including Imam al-Shafi’i himself. Such a «liberalization» of views, in our opinion, is a consequence of the influence of the authoritative Dagestani legal scholar Muhammad al-Kuduki. The present study criticizes the «jadidocentric» approach in understanding the processes of the «Islamic reformation» that took place in Dagestan at the beginning of the 20th century.